1999
DOI: 10.1056/nejm199904293401704
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Sympathetic Hyperactivity by Enalapril in Patients with Chronic Renal Failure

Abstract: Increased sympathetic activity contributes to hypertension in patients with chronic renal disease. ACE inhibition controls hypertension and decreases sympathetic hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
259
3
13

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(289 citation statements)
references
References 30 publications
14
259
3
13
Order By: Relevance
“…The role of the sympathetic nervous system is less clear. Our data show that in these patients the MSNA is often increased as well, confirming the limited available data on this issue in CRF patients (3,17). As a consequence of these findings, the logical treatment of these patients should be aimed at normalization of the fluid status and of the renin and sympathetic overactivity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The role of the sympathetic nervous system is less clear. Our data show that in these patients the MSNA is often increased as well, confirming the limited available data on this issue in CRF patients (3,17). As a consequence of these findings, the logical treatment of these patients should be aimed at normalization of the fluid status and of the renin and sympathetic overactivity.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies have evaluated the effect of ACE inhibitors on MSNA. In essential hypertension, there was no effect (18), but MSNA was reduced when both renin and sympathetic activity were activated, such as in CRF or heart failure (3,19). The present study shows that an AngII receptor blocker also reduces MSNA in CRF patients.…”
Section: Discussionmentioning
confidence: 54%
“…Also, norepinephrine levels were higher in the patients with chronic renal insufficiency and norepinephrine levels were inversely correlated with renal function. Fromthese results, sympathetic activity was found to be a contributor to hypertension in chronic renal insufficiency as Ligtenberg et al recently confirmed (34). Similar findings were also reported by Baumgart et al (32), who demonstrated significantly lower differences in blood pressure between the awake and sleeping time in patients with chronic renal insufficiency compared to control subjects.…”
Section: Aggressive Blood Pressure Reduction In Patients With Chronicsupporting
confidence: 81%
“…These two variables of blood pressure give us valuable information on the highest levels of blood pressure and on the presence or absence of the morning surge. the study of Ligtenberg et al (34), enalapril controls hypertension and decreases sympathetic hyperactivity in patients with chronic renal insufficiency. In their study, they confirmed these effects in a short period.…”
Section: Aggressive Blood Pressure Reduction In Patients With Chronicmentioning
confidence: 95%
“…An influence of sympathetic drive as an underlying pathophysiological mechanism 21 is suggested by the positive association between heart rate at baseline and new-onset diabetes mellitus observed in both treatment arms and which was statistically significant in the valsartan group. The known increased sympathetic effect of amlodipine, 22 that is, treatment-heart rate interaction may contribute to the diminished effect of heart rate as a predictor in the patients treated with amlodipine (model 4).…”
Section: Discussionmentioning
confidence: 99%